EP1245 Topical Imiquimod treatment of high-grade cervical intraepithelial neoplasia (TOPIC-3) study: a multicentre, non-randomized controlled study. (1st November 2019) - Hendriks, N; Koeneman, M; van de Sande, M; Kooreman, L; van Kuijk, S; Hoosemans, L; Sep, S; van Gorp, T; Slangen, B; Piek, J; van Beekhuizen, H; Nijman, H; et al.
Abstract : Introduction/Background: High-grade cervical intraepithelial neoplasia (CIN) is the premalignant condition of cervical cancer. Treatment is usually performed by large loop excision of the transformation zone (LLETZ), but is associated with an increased risk of premature birth in subsequent pregnancies. Topical imiquimod cream may be an alternative treatment modality. This study aims to provide evidence on treatment efficacy and side-effects of topical imiquimod cream compared to standard LLETZ treatment. Methodology: A multi-centre, non-randomized controlled trial was performed among women with a histological diagnosis of CIN 2/3. Women who opted for standard treatment, underwent LLETZ treatment. Successful treatment was defined as no need for second LLETZ after 6 months follow-up. Women who opted for imiquimod treatment, administered 6.25 mg imiquimod 5% cream vaginally up to three times per week during 16 weeks. Treatment efficacy was evaluated with colposcopy at 20 weeks follow-up and defined as CIN 1 or less. Results: 123 patients were included. 62 women underwent LLETZ treatment, which was successful in 58 women (95%). 37% of women reported severe side-effects (Visual analogue scale [VAS] ≥ 8). 61 women underwent topical imiquimod treatment. Twelve women discontinued treatment due to side effects. Treatment was successful in 27 (59%) of remaining women. Side effects were reported by all women who underwent imiquimod treatment and consisted most frequently of headache and fatigue. 69.0% of women reported severe side-effects (VAS ≥ 8). All reported side-effects can be found in tables 1 and 2. Conclusion: Topical imiquimod is a feasible alternative treatment for patients with high-grade CIN, although efficacy is considerably lower than LLETZ treatment. It could be an alternative treatment, especially for women with a future pregnancy desire. Predictive biomarkers are necessary to better select those patients who will benefit from imiquimod treatment. Disclosure: The authors declare that they have no competing interests. This study and manuscript preparation were funded by the Academic Hospital of Maastricht (Academic Fund) and MedaPharma. Both funding bodies were not involved in the study design and will not be involved in the collection, analysis, and interpretation of data, in the writing of the manuscript and in the decision to submit the manuscript for publication.